2019
DOI: 10.1103/physrevc.99.044306
|View full text |Cite
|
Sign up to set email alerts
|

Shape staggering of midshell mercury isotopes from in-source laser spectroscopy compared with density-functional-theory and Monte Carlo shell-model calculations

Abstract: Neutron-deficient 177−185 Hg isotopes were studied using in-source laser resonance-ionization spectroscopy at the CERN-ISOLDE radioactive ion-beam facility, in an experiment combining different detection methods tailored to the studied isotopes. These include either α-decay tagging or Multireflection Time-of-Flight gating to identify the isotopes of interest. The endpoint of the odd-even nuclear shape staggering in mercury was observed directly by measuring for the first time the isotope shifts and hyperfine s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 103 publications
4
28
0
Order By: Relevance
“…A detailed description of the experiment can be found in Refs. [3,4], while only the information pertinent to the present work is provided here. In our study, 180 Pt was produced in the 180 Hg → 180 Au → 180 Pt β-decay chain, shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed description of the experiment can be found in Refs. [3,4], while only the information pertinent to the present work is provided here. In our study, 180 Pt was produced in the 180 Hg → 180 Au → 180 Pt β-decay chain, shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…This value was extracted from decay data recorded during the same experiment as described in Refs. [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…For the cases where this recipe is not possible, the V MU interaction is used. Note that the V MU interaction was determined as a simple modeling to the microscopic shell-model interactions [18], and that it was used in earlier studies on Zr, Sn and Hg isotopes [20][21][22][23][24]. The dimension of the many-body Hilbert space reaches beyond 10 31 , which is formidably larger than the current limit (∼10 11 ) of the conventional CI method.…”
mentioning
confidence: 99%
“…Figure 3 shows a deeper insight in the calculation performed for 154 Sm. It includes Potential Energy Surface (PES) obtained by Hartree-Fock calculation using the same Hamiltonian with, as constraints, the quadrupole moments corresponding to specific values of β 2 and γ (their relations are explained in [23,24,36]). The latter are shape variables of the ellipsoidal shape being the magnitude and the proportion of the ellipsoid axes, respectively (see Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation